Facile one-step carbothermal reduction synthesis of Na3V2(PO4)2F3/C serving as cathode for sodium ion batteries. (1st March 2019) - Deng, Liang; Sun, Gang; Goh, Kokswee; Zheng, Li-Li; Yu, Fu-Da; Sui, Xu-Lei; Zhao, Lei; Wang, Zhen-Bo
Abstract: Na3 V2 (PO4 )2 F3 is considered to be a prospective candidate cathode for sodium ion batteries owing to its high operating voltage and excellent structural stability. However, the cycle performance together with rate capability of Na3 V2 (PO4 )2 F3 has been restrained on account of its low electronic conductivity. In this work, a series of carbon-coated Na3 V2 (PO4 )2 F3 samples were fabricated by utilizing a facile one-step carbothermal reduction method. The well crystallized Na3 V2 (PO4 )2 F3 /C showed good capacity performance where it delivered an initial discharge capacity of 112.3 mAh g −1 at 1C rate with a high retention of 89.7% after 100 cycles. Even at the current rate of 8C, it could give a capacity of 64 mAh g −1 . The cycle stability of Na3 V2 (PO4 )2 F3 /C at the high temperature of 55 °C was also demonstrated. Besides, the Na3 V2 (PO4 )2 F3 /C showed good long-term durability, of which the capacity loss averaged 0.0264% per cycle at 2C rate at room temperature. Furthermore, the electrochemical impedance spectroscopy well explained the difference about the electrochemical performance of different Na3 V2 (PO4 )2 F3 /C samples. More importantly, Na3 V2 (PO4 )2 F3 /C is of great competence to serve as cathode for future sodium ion batteries applied in energy storage systems, and this simple one-step carbothermal reduction strategy to get Na3 V2 (PO4 )2 F3 /C will make contributions to accelerating this process.